Effect of Yoga on the Quality of Life of Nurses Working in Intensive Care Units. Randomized Controlled Clinical Trial - Rostami, Khatereh; Ghodsbin, Fariba (Investigación y Educación en Enfermería, 2019)
Objective. The work, herein, sought to determine the effect of yoga on the quality of life of nurses working in intensive care units (ICU). Methods. This was a randomized controlled clinical trial of a preventive intervention of three weekly sessions of yoga exercises, which included aspects of meditation, breathing control, and slow body movements. The study selected 70 nurses working in ICU and assigned them to two groups: experimental (n = 35) and control (n = 35). The World Health Organization Quality of Life brief questionnaire (WHOQoL-Bref) was used to evaluate on four moments (baseline, one, two, six months after the start of the study); this scale has 26 items with Likert-type response options ranging from 1 to 5; higher total score indicates better quality of life. Results. The baseline score of quality of life in the experimental group was 62.3, which increased to 70.7 on the first month and continued improving in the evaluations on the second month (72.8) and sixth month (74.1), with this change being statistically significant. Instead, the control group showed no differences in scores of the different moments of evaluation (baseline = 62, first month = 61.9, second month = 62.4, and sixth month = 60.4). In the four domains of the WHOQoL-Bref (physical, psychological, social relationships, and environment), it was also noted that the experimental group obtained better scores over time compared with the control group. Conclusion. The intervention of yoga exercises was effective in improving the quality of life of nurses working in ICU. How to cite this article: Rostami K, Ghodsbin F. Effect of Yoga on the Quality of Life of Nurses Working in Intensive Care Units. Randomized Controlled Clinical Trial. Invest. Educ. Enferm. 2019; 37(3):e06.